The Effect Of Pregnant Women Empowerment To Achıeve The Nutrıtıon Fulfıllment Based On Balanced Nutrıtıon Prıncıples Towards The New Borns Nutrıtıon Status - Zuraidah Nasution, Ida Nurhayati, Eva Fitriyaningsih (International Journal of Advanced Science and Technology, 2020)
This study used the Quasi Experimental method and was designed with the Untreated Control Group Design with Pretest and Posttest. The intervention given to the sample was an empowerment through nutrition counseling about the food consumed based on balanced nutrition guidelines. This research was carried out through food recall before the intervention, then pregnant women were given thr interventions for 3 (three) months and then the food consumption was recalled before the delivery. After the baby was born, the data on the babies’ birth weight were collected. This research was conducted in Deli Serdang District and Aceh Besar District with 127 pregnant women as samples, 63 pregnant women in Deli Serdang Regency and 64 in Aceh Besar District. Through the study it was found that pregnant women in the intervention group experienced an increase in nutritional knowledge 1.81 times and were able to fulfill their nutritional needs 2.06 times compared to groups that did not get the empowerment. Increased protein and carbohydrate intake and nutritional status of pregnant women could affect the nutritional status of the newborns, using the newborn weight as an indicator. The empowerment interventions increased the mothers’ nutrition knowledge and encouraged pregnant women to improve the quality and quantity of their food consumption so that they can meet their nutritional needs which can eventually give birth to babies with normal weight or nutritional status.